The Principal's Transformative Leadership Model in Resulting Competitive Graduates - Nur Uhbiyati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This article investigated the principal’s transformative leadership efforts in developing school organizational culture to realize competitive graduates. The data were collected by in-depth interview technique to the principal who was a primary data source; while educators, educational staffs, and students were secondary data sources. The data from the primary data source were cross-checked its correctness to the secondary data source (data source triangulation). This article unveiled some important findings from the research. The principal’s transformative efforts to preserve and develop school organizational culture were artifacts, symbols, systems of values, norms and assumptions, beliefs, religions. The result contributed to formal education institutions, where the principal’s transformative leadership model to realize competitive graduates consists of some aspects, namely: input, process, output, and continuous feedback. The model initially derived from transformative leadership management in the field of enterprise applied in educational institutions and was successful in realizing quality graduates having high competitiveness at national and global levels. Keywords: Transformative Leadership Model, Competitive Graduate, Principal Leadership